Percutaneous cystolithotripsy for patients with benign prostatic hyperplasia - M. E. Topuzov (Vestnik Urologii, 2021)
Introduction. According to the literature, 5.0% of patients with urolithiasis are characterized by the presence of stones in the bladder. The issue of bladder stones for patients with benign prostatic hyperplasia remains relevant and requires further improvement of approaches to surgical treatment.Purpose of the study. To evaluate the safety and efficacy of energy-diverse percutaneous cystolithotripsy (and placement of a cystostomy catheter) in comparison with transurethral cystolithotripsy.Materials and methods. A retrospective analysis of 56 cases in patients (aged 54-82 years) with bladder stones was carried out. All patients were treated in the Urology Clinic of the Mechnikov North-Western State Medical University from 2019 to 2021. Two groups were formed: group I — 26 (46.4%) patients who underwent percutaneous cystolithotripsy, group II — 30 (53.6%) patients underwent transurethral cystolithotripsy. The duration of surgery, intraoperative and postoperative complications were assessed.Results. On average, the duration of surgery for the percutaneous approach was shorter than for transurethral access (35 vs 44 min). The stone-free rate in the case of the percutaneous approach was 100.0%, while in transurethral cystolithotripsy the stone-free rate was 90.0%. In the early postoperative period, in groups I and II, gross hematuria was observed for 2 (7.6%) and 4 (13.3%) patients, respectively. In the late postoperative period, 2 patients from group II had a urethral stricture.Conclusions. Percutaneous cystolithotripsy is a minimally invasive method of stone fragmentation, characterized by a minimal risk of intra- and postoperative complications.